Effects of filter materials on the removal efficiency of phosphorus and nitrogen from wastewater in an enhanced AO-BAF system - YAN, Zichun; Iseghayan, Nosakhare (Kuwait Journal of Science, 2017)
Phosphorus and nitrogen are some of the major nutrients easily found in waste water that pollutes our water bodies resulting to eutrophication. For years, economical and effective ways have being sort after to reduce the influx of these nutrients into our water waters. Biological Aerated Filter (BAF)technology have been one of them, but some challenges have been found to affect the removal efficiency of phosphorus and nitrogen through the use of an ordinary AO BAF system. In that, the effluents from a normal AO BAF system hardly meets the environmental standard of effluents discharge into the local water bodies. The research objective of this study is to determine the best condition for phosphorus and nitrogen removal in an enhanced AO BAF system, and the role of filter materials on the removal efficiency will be investigated, if the effluents meet with the environmental standards. The AO BAF and the sponge iron and manganese sand system filter materials were composed of ceramic, zeolite, sponge iron and manganese sand. The following setting parameters were used: Reflux ratio was set at 100% and 200%, Hydraulic load at 0.5 m3 / m2 • h., Air/Water ratio at 10:1 and the use of ceramic, zeolite, sponge iron and manganese sand filter materials. The removal efficiency of phosphorus and nitrogen on various settlings and filters materials were compared at the end of the experiment. And it was shown that sponge iron mixed with manganese sand materials recorded more removal efficiency of phosphorus which meet the environmental standards of phosphorus effluents discharge into local water bodies.